Thermal and Moisture Effects on the properties and Aerodynamics Grains with Video Tracker Analysis - RISMAWATI (NIM : 90214008), ELY
The behavior of particles in the air flow depending on the aerodynamic properties of the particle. The aerodynamic forces that exist during the relative motion between the air and different materials each different particle. Aerodynamic properties are affected by moisture. Grains have the ability to absorb water called by imbibition. Terms of the imbibition that the pressure difference between the seeds with water, where the water pressure is less than the pressure of the seeds, there is the power of attraction between the water and the specific seed. The addition volume in the event of imbibition is smaller than the sum of the volume of the substance at first, with substances that diimbibisikan when in a free state. This difference is expected because substances or molecules that imbibitions must occupy space between molecular substances so that the volume of substances imbibition less depressed than when in a free state. The amount of water absorbed during imbibition process are generally small and fast. This study examines the influence of thermal effects and moisture content of the nature and aerodynamics grains with video tracker analysis. This method utilizes a microwave. Grains were given three treatments, namely immersion, soaking and heating, and drying. Analysis in this research include the relationship between the absorption of grains against time, the relationship between the absorption of grain to temperature, and the relationship between the water content of the correction factor is aerodynamics. Results of this study was to determine the absorption of grain when the soak, given the effects of heat and drying as well as linking to the properties and aerodynamics grains with video tracker analysis.